Amiloidose primária associado a mieloma de cadeias leves kappa. - Raquel G Martins; Roberto Roncon-Albuquerque; Raquel Cabral; João Frazão; Pedro Von Hafe (Acta Médica Portuguesa, 2010)
The clinical spectrum of plasma cell dyscrasias includes primary amyloidosis and multiple myeloma. These two entities are present at the time of diagnosis in 10 percent of cases.A 72 years old female was admitted to our Institution with oligoanuric renal failure. Renal ultrasonography revealed normal kidney dimensions, with a slight decrease in the normal parenchyma-sinus differentiation. The complementary study identified free kappa light chains in urine (73,9 mg/dL) and bone marrow study fulfilled the criteria for multiple myeloma. Search for amyloid fibrils in abdominal subcutaneous fat was positive. The serum beta-2 microglobulin level was elevated (26 mg/L). Transthoracic echocardiogram did not reveal pathologic findings. Treatment initiation was complicated by hemodialysis catheter-associated Staphylococcus aureus infection.Primary amyloidosis associated with light chain myeloma is a rare, and often late, diagnosis with a dismal prognosis. Renal failure is a frequent initial presentation of the disease and infection an important cause of death.